Consistently Low Levels of Osteocalcin From Late Pregnancy to Postpartum Are Related to Postpartum Abnormal Glucose Metabolism in GDM Patients - Gong, Yujia; Li, Na; Lai, Mengyu; Fang, Fang; Yang, Jiaying; Kang, Mei; Shen, Tingting; Peng, Yongde; Wang, Yufan (Frontiers in Endocrinology, 2022)
Objective: Increasing evidence suggests that osteocalcin (OC), a marker of bone formation, plays an important role in glucose homoeostasis. Few studies have investigated the relationship between OC levels in gestational diabetes mellitus (GDM) patients and their postpartum glucose metabolism. This study evaluated the relationship between OC levels in late pregnancy, their longitudinal changes, and postpartum glucose metabolism among GDM patients. Measures: Serum OC was measured in late pregnancy and the postpartum period for 721 GDM patients. All patients underwent a 75-g oral glucose tolerance test (OGTT) at 6–8 weeks postpartum. According to postpartum OGTT outcomes, patients were categorized into abnormal glucose metabolism (AGM) (n=255) and normal glucose tolerance (NGT) groups (n=466). Glucose metabolism-related indices were measured and calculated. Logistic regression analysis and linear mixed-effects model were used to assess the association between OC and postpartum AGM. Results: In late pregnancy, OC levels were lower in the AGM group than in the NGT group (13.93±6.90 vs 15.33±7.63 ng/ml, P=0.015). After delivery, OC levels increased in both groups. However, OC levels remained lower in the AGM group than in the NGT group (23.48±7.84 vs 25.65±8.37 ng/ml, P=0.001). Higher OC levels in late pregnancy were associated with decreased risk of progressing to postpartum AGM (OR:0.96, 95%CI:0.94–0.99). Linear mixed-effects analysis showed that postpartum AGM patients exhibited consistently lower OC levels than NGT group from late pregnancy to the postpartum period after adjustment for cofactors (β=-1.70, 95% CI: -2.78– -0.62). Conclusions: In GDM patients, consistently low levels of OC from late pregnancy to postpartum were associated with increased postpartum AGM risk. The increase in serum OC may act as a protective factor to curb the progression of AGM at postpartum for GDM patients.